Bidentate Rh(I)‐Phosphine Complexes for the C−H Activation of Alkanes: Computational Modelling and Mechanistic Insight. Issue 18 (18th August 2022) - Huang, Tianbai; Kupfer, Stephan; Richter, Martin; Gräfe, Stefanie; Geitner, Robert
Abstract: The C−H activation and subsequent carbonylation mediated by metal complexes, i. e., Rh(I) complexes, has drawn considerable attention in the past. To extend the mechanistic insight from Rh complexes featuring monodentate ligands like P(Me)3 towards more active bisphosphines (PLP), a computationally derived fully conclusive mechanistic picture of the Rh(I)‐catalyzed C−H activation and carbonylation is presented here. Depending on the nature of the bisphosphine ligand, the highest lying transition state (TS) is associated either to the initial C−H activation in [Rh(PLP)(CO)(Cl)] or to the rearrangement of the chloride in [Rh(PLP)(H)(R)(Cl)]. The chloride rearrangement was found to play a key role in the subsequent carbonylation. A set of 20 complexes of different architectures was studied, in order to fine tune the C−H activation in a knowledge‐driven approach. The computational analysis suggests that a flexible ligand architecture with aromatic rings can potentially increase the performance of Rh‐based catalysts for the C−H activation. Abstract : Computational ligand evaluation : Mechanistic insights into the C−H activation of alkanes and the subsequent formation of the respective aldehyde as mediated by a set of 20 bidentate phosphine‐based Rh(I) complexes.